2016
DOI: 10.4143/crt.2014.312
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods of Lymph Node Evaluation for Predicting the Prognosis of Colorectal Cancer Patients with Inadequate Lymph Node Harvest

Abstract: PurposeLymph node metastasis is an important factor for predicting the prognosis of colorectal cancer patients. However, approximately 60% of patients do not receive adequate lymph node evaluation (less than 12 lymph nodes). In this study, we identified a more effective tool for predicting the prognosis of patients who received inadequate lymph node evaluation.Materials and MethodsThe number of metastatic lymph nodes, total number of lymph nodes examined, number of negative metastatic lymph nodes (NL), lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Preoperative detection of lymph node (LN) metastases in patients with rectal cancer is crucial for selection of the appropriate treatment strategy. LN involvement has also been shown to be a major prognostic factor in determining the risk of recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative detection of lymph node (LN) metastases in patients with rectal cancer is crucial for selection of the appropriate treatment strategy. LN involvement has also been shown to be a major prognostic factor in determining the risk of recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, determining the status of LNs is the main determinant of adjuvant chemotherapy [5,9]. Multiple large studies have shown that the LNM rate (LNR) is an important predictive factor for estimating the prognosis of CRC [2,10,11]. Therefore, adequate and accurate LN status assessment and prediction are important for treatment decision making and prognostic evaluation in CRC.…”
mentioning
confidence: 99%
“…Yet, this did not increase the risk of anastomotic leakage or urinary disturbance in our patients (data not shown). IMA root dissection contributed to the average yields 26-27 lymph nodes, affording more accurate postoperative CRC staging (20).…”
Section: Discussionmentioning
confidence: 99%